into neVeRland - Tan, Yuki (Nanyang Technological University, 2023)
into neVeRland is a phygital puzzle game. It involves using a headset to extend and bridge the physical world, portrayed using AR (Augmented Reality), with the digital world, portrayed using VR (Virtual Reality). Portals are the main element that bridges these two realities, allowing for a seamless transition and transporting the player to worlds of fairy tales and fantasy.